2015
DOI: 10.1128/jvi.02507-14
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of Kaposi's Sarcoma-Associated Herpesvirus during De Novo Primary Infection of Human B and Endothelial Cells

Abstract: Kaposi's sarcoma-associated herpesvirus (KSHV), also called human herpesvirus 8 (HHV8), is a double-stranded DNA virus that causes Kaposi's sarcoma, primary effusion lymphomas, and multicentric Castleman's disease (1-3). Like other herpesviruses, KSHV exhibits both latent and lytic modes of infection, persisting predominantly in the latent state in which only a subset of the viral proteins are expressed, including the latency-associated nuclear antigen (LANA) protein (4-8). Although the expression of latent pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
52
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 49 publications
2
52
0
Order By: Relevance
“…We verified these findings by infecting PBMCs with KSHV. Interestingly, due to the dynamic status of latency and lytic replication at different stages during primary infection (26,(28)(29)(30), STAT6 phosphorylation was upregulated at the early stages following infection and subsequently downregulated, suggesting that higher levels of phosphorylated STAT6 could be required for establishment but not maintenance of KSHV latency. Consistent with our and others' previous works (24,25), the robust activation of STAT6 at early stages during KSHV primary infection could contribute to viral lytic replication and gradually be reduced to a lower extent (probably due to shutoff of potent IL-4 induction and continued mild IL-13 induction, as we have observed so far) along establishment of latency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We verified these findings by infecting PBMCs with KSHV. Interestingly, due to the dynamic status of latency and lytic replication at different stages during primary infection (26,(28)(29)(30), STAT6 phosphorylation was upregulated at the early stages following infection and subsequently downregulated, suggesting that higher levels of phosphorylated STAT6 could be required for establishment but not maintenance of KSHV latency. Consistent with our and others' previous works (24,25), the robust activation of STAT6 at early stages during KSHV primary infection could contribute to viral lytic replication and gradually be reduced to a lower extent (probably due to shutoff of potent IL-4 induction and continued mild IL-13 induction, as we have observed so far) along establishment of latency.…”
Section: Discussionmentioning
confidence: 99%
“…3A, compare lane 2 and 5 with lanes 3 and 6, respectively), further supporting the direct link between KSHV and p-STAT6 C activation in PEL cells. Previous studies showed that KSHV primary infection usually involves a mixture of latent and lytic replication statuses within 7 days, shuts off lytic replication at about 3 days postinfection, and establishes dominant latency at about 5 days postinfection (26,(28)(29)(30). To further confirm that phosphorylated STAT6 is regulated by KSHV infection, we performed primary infection of human peripheral blood mononuclear cells (PBMCs), followed by immunoblotting analysis against STAT6 and phosphorylated STAT6.…”
Section: Kshv Induces Constitutive Phosphorylation Of Stat6 (P-stat6 mentioning
confidence: 99%
“…In support of the potential to produce small peptides (Ͻ100 amino acids), a portion of T1.5 is found in the cytoplasm by Northern blotting and by RNA fluorescence in situ hybridization (FISH) (21), whereas T3.0 produces at least three small peptides (41), one of which induces its antisense transcript RTA (43). PAN RNA and T1.5 are also packaged within virions and expressed in the early stages of primary infection, suggesting an important role in establishing a successful infection (35,36). Two other lncRNAs, ALT (antisense-to-latency transcripts) and T6.1, have been consistently observed in transcriptome sequencing (RNA-seq) surveys.…”
mentioning
confidence: 99%
“…Its origin and regulation has been well characterized (22,(25)(26)(27)(28)(29)(30)(31)(32). In situ studies showed that PAN RNA is either not expressed or expressed at low basal levels during latency (33,34) and then is induced to higher levels during lytic reactivation; however, PAN RNA is either the most abundant or among the most abundant transcripts during de novo infection (35,36). PAN RNA has been reported to inhibit the expression of immune response genes such as interleukin-4 and gamma interferon, to interact with several viral and cellular proteins, to act as a global regulator of viral genes by interacting with cellular transcriptional regulators and chromatin-modifying proteins, and to potentially encode small peptides from noncanonical open reading frames (ORFs) (13,(26)(27)(28)(29)(37)(38)(39).…”
mentioning
confidence: 99%
“…This suggests the existence of an additional, proteasome-independent mechanism for degradation of SP100 and PML. These observations indicate that in cells that support efficient lytic replication, in addition to virion-associated proteins, de novo-synthesized gene products, perhaps from copackaged viral mRNA delivered with the viral particle (25) or from very early transcripts, can contribute to the degradation of SP100 and, in particular, of PML. An attractive hypothesis would be that early gene products of RRV contribute to degradation of SP100 and PML and induce their nonproteasomal degradation, in addition to the effects of the tegument protein ORF75.…”
Section: Discussionmentioning
confidence: 99%